THE MESSAGE OF RELIGIOUS MODERATION IN TANBIH QADIRIYAH NAQSYABANDIYAH (TQN) PONDOK PESANTREN SURYALAYA - Muhamad Dani Somantri; Dahwadin Dahwadin (Teosofia: Indonesian Journal of Islamic Mysticism, 2019)
Lately contradictory attitude toward a variety of social maturity often practiced in religious life, state and nation. Characterized by increasing the ideology of intolerance, claims of truth, apathy, radicalism, terrorism, and violence, racial background which would almost the stability of national unity of Indonesian. Efforts to push the level of socio-religious intolerance becomes the collective responsibility, one through the strengthening of research-based schools of religious moderation both theoretical and practical.The significance of this study is to track messages of religious moderation contained in the manuscript Tanbih TQN Boarding School Suryalaya Tasikmalaya. Type a descriptive qualitative research methodology to approach the content analysis study (content analysis) to the data source.The research found that the manuscript is a testament mursyid Tanbih Sheikh Abdullah Mubarak bin Nur Muhammad (Abah Sepuh) to all the brothers TQN Suryalaya. To obtain the inner and outer happiness and safety of life hereafter in accordance with the purpose bertarekat, then the text Tanbih true not only seen as sakralitas to be read and heard in every activity TQN Boarding School Suryalaya brothers, but also must be realized in the social life. Because the script Tanbih containing messages of religious moderation in the life of the nation which includes: (1) harmonization of the relationship between religion and state; (2) an attitude of respect and appreciate people who are older (seniority); (3) mutual compassion in the form of mentoring, guiding, and advising the kindness to younger (junioritas); (4) humility to an equal; (5) always put the collective interest above the interests of individual / group; (6) the attitude of generous, virtuous, and warm-hearted towards the poor; and (7) maintain the environment so maintained continuity.